pir-hsa-216911 inhibit pyroptosis in hepatocellular carcinoma by suppressing TLR4 initiated GSDMD activation - Zhouxiang Liao; Lichao Yang; Xiaojing Cheng; Xuejing Huang; Qi Zhang; Daoqiang Wen; Zhenyu Song; Yasi Li; Sha Wen; Yongfeng Li; Meizhen Ou; Zhangnan Huang; et al. (Cell Death Discovery)
Abstract Hepatocellular carcinoma (HCC) is a global health concern, ranking as the fourth leading cause of cancer-related deaths worldwide. However, the role of piwi-interacting RNAs (piRNAs) in HCC processes has not been extensively explored. Through small RNA sequencing, our study identified a specific piRNA, pir-hsa-216911, which is highly expressed in HCC cells. This overexpression of pir-hsa-216911 promotes HCC cell invasion and inhibits cell death, particularly pyroptosis. Knocking out pir-hsa-216911 led to increased cell pyroptosis activity, resulting in the activation of caspase-1 and GSDMD. Further analysis revealed that pir-hsa-216911 targets and suppresses TLR4, a key gene associated with pyroptosis in HCC. In the Huh7 cell line, pir-hsa-216911 knockout confirmed its role in suppressing the TLR4/NFκB/NLRP3 pathway by silencing TLR4. Knocking out pir-hsa-216911 significantly inhibited the formation of Huh7 xenograft tumor. In HCC patients, pir-hsa-216911 was highly expressed in HCC tumor samples with steatosis, suppressing TLR4 expression and inhibiting GSDMD activation. This study introduces pir-hsa-216911 as a new high-expressing piRNA in HCC, which inhibits pyroptosis by silencing TLR4 to suppress GSDMD activation. These findings have significant implications for HCC molecular subtyping and as a potential target for cancer therapy.